Effect of drought stress during critical developmental stages on morphological and grain yield-related traits in winter barley (Hordeum vulgare L.). - Zita Berki; Tibor Kiss; Judit Bányai; András Cseh; Krisztina Balla; Ildikó Karsai (PLoS ONE)
As the frequency of droughts increases, the breeding of new drought-tolerant cereal varieties may become increasingly important. However, the complex effects of drought stress on grain yield-related traits are difficult to study precisely, and relatively little information is available on how drought during flowering affects plants. Therefore, 28 winter barley cultivars were included into controlled environmental tests, where their reactions were determined to single drought stress treatment applied at heading and to combined drought stresses applied at first node appearance and then at heading. Drought stress (both single and combined) significantly reduced all of the grain-yield related traits. Notably, grain yield was reduced by 48% in the two-row varieties and by 44.24% in the six-row varieties under combined drought stress, compared to the control. Our study has also demonstrated, that the combined application of drought tolerance/susceptibility indices (DT/SIs) and BLUP-based analysis provides a reliable approach for identifying stress-tolerant genotypes. We identified two main types of drought stress tolerance: the ability of preserving grain number and weight in the main ears, in parallel of maintaining the number of reproductive tillers (more tolerant), and the ability of preserving grain number and weight in the side ears (least tolerant). Both types appeared in either treatment, but not with the same intensity. Our results may provide useful information for a better understanding of this topic, which may become even more important in the context of increasingly frequent droughts.